Organization and representation of informal workers in São Tomé and Príncipe: state agency and sectoral informal alternatives - Rodrigues, C. U.; Bialoborska, M. (African Studies Quarterly, 2017)
In São Tomé and Príncipe, both the size of the informal economy and the scope of the mechanisms of organization and representation are little known. A research conducted recently showed that the almost always limited and irregular incomes generated in this sector are also associated with precarity and a lack of social protection mechanisms. While initiatives led by the state and supported by international funders positioned unions as privileged organizations for representing and supporting the workers in this sector, the limited results generated opportunities for the creation of sectoral bottom-up initiatives. The discussion is then focused on the areas addressed by the initiatives of specific sectors and types of activity - taxi and motorbike drivers and money exchangers - comparing the outcomes with those of the unions in terms of increased social protection and representation.